School Staff Perceptions of Connectedness with Students in a Low-Income Public Middle School: Implications for School Nursing Practice - Pestaner, Mitzi C (East Carolina University, 2021)
School connectedness, defined as the belief by students that adults and peers within the school care about them and their learning, has been found to be a protective factor against suicidal thoughts and behaviors among adolescents. Since suicide is the second leading cause of death for ages 10-14, school connectedness is important for adolescent health. School connectedness can be fostered with trusting relationships within a positive school climate. While school nurses are positioned to collaborate with school staff in suicide interventions, there is minimal evidence of collaborative interventions cited within the literature. The purpose of this study was to examine the experiences of teachers and support staff that explain their perceptions of school climate and feeling connected to students and discuss implications for school nursing practice. A sequential explanatory mixed-methods secondary data analysis was conducted, guided by Bronfenbrenner's bioecological theory of human development. The site for the primary study was a rural public middle school in the Southeast United States. The quantitative data were obtained from a convenience sample of 6th, 7th, and 8th grade core and electives teachers (n = 14) and support staff (n = 5) who completed the Teacher School Connectedness Survey. Descriptive statistics were used to examine the culture related to school climate and connectedness. The qualitative data were obtained from five focus group transcripts with teachers (n = 20) and support staff (n = 6). Qualitative data were analyzed using in Vivo and Focused Coding. Themes were developed using thematic analysis. The quantitative and qualitative results diverged. The quantitative data revealed that more than half of the respondents described the climate as warm/positive and all felt positively connected to students. The major themes from the qualitative data, cloud of chaos, snowballing, and pushing through the fog, describe an environment characterized by disruptive, aggressive, and withdrawn student behaviors. The results suggest lower levels of connectedness and a school climate not conducive to fostering connectedness. Student behaviors may be masking underlying mental health issues, such as depression, a risk factor for suicide. Implications for school nursing practice to enhance school connectedness are discussed.
Keywords: school connectedness; school climate; suicide; protective factors; adolescents; School Nursing; Schools; Students